2017
DOI: 10.3748/wjg.v23.i15.2785
|View full text |Cite
|
Sign up to set email alerts
|

Age-related impairment of esophagogastric junction relaxation and bolus flow time

Abstract: AIMTo investigate the functional effects of abnormal esophagogastric (EGJ) measurements in asymptomatic healthy volunteers over eighty years of age.METHODSData from 30 young controls (11 M, mean age 37 ± 11 years) and 15 aged subjects (9 M, 85 ± 4 years) were compared for novel metrics of EGJ-function: EGJ-contractile integral (EGJ-CI), “total” EGJ-CI and bolus flow time (BFT). Data were acquired using a 3.2 mm, 25 pressure (1 cm spacing) and 12 impedance segment (2 cm) solid-state catheter (Unisensor and MMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Our data suggest that EGJ‐CI is not affected by age, which agrees with a report by Cock et al, who noted similar EGJ‐CI in younger and older individuals, even at ages higher than those evaluated in this study 22 . In contrast, when grouping by sex, female volunteers had higher EGJ‐CI and conventional LES pressure metrics using the Medtronic system (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data suggest that EGJ‐CI is not affected by age, which agrees with a report by Cock et al, who noted similar EGJ‐CI in younger and older individuals, even at ages higher than those evaluated in this study 22 . In contrast, when grouping by sex, female volunteers had higher EGJ‐CI and conventional LES pressure metrics using the Medtronic system (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…3 This lack of consistency suggests that EGJ-CI is best utilized as an adjunctive metric rather than providing a definitive zone of normality, consistent with the Lyon consensus recommendation. 5 Our data suggest that EGJ-CI is not affected by age, which agrees with a report by Cock et al, who noted similar EGJ-CI in younger and older individuals, even at ages higher than those evaluated in this study 22 . In contrast, when grouping by sex, female volunteers had higher EGJ-CI and conventional LES pressure metrics using the Medtronic system (Table 2).…”
Section: Given Recognition Of CD Contribution and Respiratory Variationsupporting
confidence: 93%
“…Eleven pharyngeal [10,34,39,43,44,45,46,47,48,49,50] and sixteen esophageal studies [23,24,25,51,52,53,54,55,56,57,58,59,60,61,62] were identified and results described in Table 3 (summary) and Table 4 (measurements).…”
Section: Resultsmentioning
confidence: 99%
“…Similar changes were also seen in relation to participant age and BMI, suggesting that these factors also increase esophageal emptying resistance. Based on previous studies, older age has shown to reduce esophageal compliance and neurogenic relaxation of the LES, while higher BMI results in higher gastric pressure due to increased abdominal fat …”
Section: Discussionmentioning
confidence: 99%